PENILAIAN RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN METODE HIRARC PADA PEKERJAAN DI PENGGILINGAN PADI - Mayadilanuari, Aerrosa Murenda; Nurvita, Silvia; Kurniawan, Dhieo (Poltekkes Kemenkes Bandung, 2025)
The rice milling industry is an important component in the national economy and employment absorption. However, based on data from the Indonesian Ministry of Manpower in 2023, the number of work accident cases in Indonesia was recorded at 370,747 cases. This illustrates that industrial work faces various occupational safety and health (K3) risks, so hazard identification and risk assessment are needed. UD. X rice milling in Semarang City is an informal industry with 16 workers. The purpose of this study was to identify hazards and assess OHS risks using the Hazard Identification Risk Assessment and Risk Control (HIRARC) method. This research was conducted in the rice milling industry UD. X in Semarang City from April to May 2024. The type of qualitative descriptive research was used in this study with 6 respondents determined by purposive sampling. The research instruments consisted of interview sheets, observation sheets, and HIRARC sheets. The interview technique used was in-depth interviews with source triangulation. The analysis showed 21 potential hazards, with the highest risk found in the rice milling process stages 1 and 2, as well as the rice packaging process. The results of controlling the potential hazard risks at UD. X are not optimal and need immediate improvement. Recommendations related to improving the work environment, regular worker training, and strict implementation of standard operational procedure (SOP) are needed to reduce the risk of accidents and occupational diseases